POLA KONSUMSI PANGAN MASYARAKAT SEKITAR KAWASAN HUTAN DI KABUPATEN TAKALAR - Idham Adha; Ida Rosada; St Sabahannur (Percetakan Umi Toaha Makassar, 2019)
The main objective of this study is to examine the demographic, social and economic characteristics of farm households around the forest area, analyze the household food consumption patterns and analyze the relationship between food consumption patterns with the characteristics of farm households in the vicinity of the forest area. This research was conducted in Takalar Regency, namely in Kale Ko’mara Village, Polongbangkeng Utara District, starting in July October 2018. Types of data used are primary data and secondary data with the number of respondents as many as 40 farmers around the forest area. The data that has been collected is analyzed using qualitative analysis and quantitative analysis. The results showed that the demographic, social and economic characteristics of farmers around the area were: 1) the age of the respondents was in the age range of 40-50 years (60.00%), 2) the highest number of family dependents was 3-4 people (65.00% ), 3) the dominant education level is elementary school / equivalent (55.0%), 4) the type of side jobs are generally planters (62.50%), 5) the longest experience of farming in the range of 20-30 years, (60.00% ), 5) the biggest income is Rp. 2,000,000-Rp.3,000,000 / Month (52.50%), 6) and the highest average expenditure is Rp. 1,500,000 - Rp. 3,000,000 (90.0%). The food consumption pattern is in accordance with the Hope Food Pattern (PPH) score of 97.8 which means that the distribution and availability of food for households is guaranteed with the composition and availability of adequate food ingredients, influenced by factors of age, income and expenditure characteristics significantly and the educational characteristics factor is very real. The characteristics of the number of family dependents, type of work and experience of farming do not have a significant effect on the patterns of food consumption of farm households around the forest area.